Analysis of Job Satisfaction Effect on Customer Satisfaction Through Employee Performance as A Mediation Variables in PT Grand Dafam Bela Ternate - Abdullah W. Jabid; Prince Charles Heston Runtunuwu; Ruslan Kamis; Novelia Falensia Makapuas (AIBPM Publisher, 2020)
This study aims to determine the effect of: 1) job satisfaction on customer satisfaction; 2) employee performance on customer satisfaction; 3) job satisfaction on employee performance; 4) job satisfaction on customer satisfaction through employee performance as the mediating variable at PT Grand Dafam Bela Ternate. This study involved 65 employees as the research samples, aided with SmartPLS 3.0 as the statistical test tool. The results showed: 1) significant job satisfaction on employee performance at PT Grand Dafam Bela Ternate. (2) Job satisfaction is not fulfilled to Customer Satisfaction at PT Grand Dafam Bela Ternate. (3) Employee performance is not in accordance with customer satisfaction at PT Grand Dafam Bela Ternate. (4) Job Satisfaction is not to customer satisfaction through employee performance as a mediating variable at PT Grand Dafam Bela Ternate.